Implementasi Edumu dalam Penilaian Akhir Semester untuk Meningkatkan Motivasi Belajar - Solihin Solihin; Fitri Nur Mahmudah (Jurnal Syntax Admiration, 2024)
The rapid development of technology has had a positive impact on every element in society. The use of sophisticated information technology is no exception, which is increasingly in demand by every individual and organization. In this research, the use of technology, information and communication through Edumu is expected to increase student achievement. The participation of parents in supervising learning through edumu which is directly connected is expected to be a separate motivation for students when preparing for the final semester assessment. Teachers can directly communicate with parents regarding student readiness through assessment results which can be submitted at any time which are used as evaluation material to improve learning achievement. This research was conducted using a qualitative method through a case study approach at SMP Muhammadiyah 2 Balikpapan. The reason for using this method and approach is that information is extracted and obtained through interviews with sources, namely the school principal, while teachers and students fill out questionnaires via Google forms related to using edumu, responses to using edumu for end-of-semester assessments and the impact of using edumu in end-of-semester assessments. The results of this study are that the use of edumu in assessment is only able to increase student learning motivation but the increase in learning achievement cannot be seen with certainty.